Lar Sênior: Instituição de Longa Permanência para Idosos - Nonaka, Camila (Brasil, 2025)
This paper addresses the lack of public architectural facilities that adequately meet the needs of the elderly population, focusing on the city of Manaus. Considering the context of population aging and the influence of inclusive architecture on the quality of life and well-being of this age group, a proposal for housing facilities was developed to meet the specific demands of this population. The research was based on a theoretical survey on the subject, case studies, and analysis of standards and technical parameters aimed at architecture for the elderly. The proposal considers practical and emotional aspects, such as environmental quality and identification with the space, and aims to promote a sense of community and social belonging, in addition to ensuring autonomy, safety, and comfort for the elderly in a society driven by productivity and workforce.